2022
DOI: 10.3390/children9111786
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Variations between Those Playing More and Those Playing Less Time in the Matches: A Case-Control Study in Youth Soccer Players

Abstract: The purpose of this study was (i) to compare two groups (players with more vs. less match play time) regarding body composition, vertical and horizontal jumping performance, and aerobic capacity; and (ii) to test the relationships between physical fitness and play time. This study followed a case-control design in which the outcome was playtime, and the causal attribute was physical fitness. Sixty-six youth male soccer players from under-16 (n = 21), under-17 (n = 19), under-18 (n = 12), and under-19 (n = 14) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…However, no significant differences and correlations are reported at the level of anaerobic power (vertical and horizontal jumps) or for Body fat between the two studied categories. For the U19 group, 740cm are obtained in the triple hop test and 40cm in the CMJ, the fitness level being better with advancing age [53]. The triple hop test performance is superior to all the average values obtained by our groups, a possible explanation being the exclusive presence of performance athletes, within our subgroups there are also students who are not constantly involved in performance sports.…”
Section: Pedagogymentioning
confidence: 48%
“…However, no significant differences and correlations are reported at the level of anaerobic power (vertical and horizontal jumps) or for Body fat between the two studied categories. For the U19 group, 740cm are obtained in the triple hop test and 40cm in the CMJ, the fitness level being better with advancing age [53]. The triple hop test performance is superior to all the average values obtained by our groups, a possible explanation being the exclusive presence of performance athletes, within our subgroups there are also students who are not constantly involved in performance sports.…”
Section: Pedagogymentioning
confidence: 48%
“…Moreover, 30 m sprint performance was significantly correlated with body fat mass. These findings are particularly important for women's soccer, as it has been previously stated that aerobic fitness can be highly correlated with participation and match-play [50]. Also, Oliveira et al [7] showed that body composition characteristics improved over the season in women's soccer.…”
Section: Discussionmentioning
confidence: 80%
“…This is particularly pertinent in the case of SSG, where heterogeneity is inherent due to the dynamic nature of the games. Furthermore, the fact that some players acted as starters while others did not may play a particular role in the adaptations (Silva et al, 2022;Janusiak et al, 2024), although the average time played in non-official matches was similar across the groups. Furthermore, while the study primarily focused on physical performance outcomes, it did not assess other relevant factors such as tactical, technical, or psychological variables.…”
Section: Discussionmentioning
confidence: 94%